APLIKASI PENGELOLAAN DAN PENGARSIPAN SURAT UMUM PADA KELURAHAN BUKIT LAMA PALEMBANG - M. Afdhaluddin (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The purpose of making a Desktop-based application in Bukit Lama Palembang village that has been made is to help the admin and service staff of the village and Lurah to be able to find out who the residents who submit letters every month and manage the data of residents who submit letters can be archived well, and can find out the process of making Letters has been there until where . This desktop application is one of the calculation media in calculating the progress of services to citizens .Making this desktop application is made with supporting applications, namely Netbeans and for database design using the My SQL application. The writing methodology used is an iterative method by observing the running system, conducting interviews and collecting data to produce the information needed. The results of making this desktop application can help the admin to make a report on anyone filing a letter and what letters are made.